2013
DOI: 10.1186/1756-8722-6-74
|View full text |Cite
|
Sign up to set email alerts
|

The role of PD-1 and PD-L1 in T-cell immune suppression in patients with hematological malignancies

Abstract: T-cell activation and dysfunction relies on direct and modulated receptors. Based on their functional outcome, co-signaling molecules can be divided as co-stimulators and co-inhibitors, which positively and negatively control the priming, growth, differentiation and functional maturation of a T-cell response. We are beginning to understand the power of co-inhibitors in the context of lymphocyte homeostasis and the pathogenesis of leukemia, which involves several newly described co-inhibitory pathways, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
214
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(219 citation statements)
references
References 52 publications
3
214
0
2
Order By: Relevance
“…PD-1 is expressed on activated T cells and interacts with its ligands PD-L1 (B7-H1) and PD-L2 (B7-DC), leading to the reduced proliferation, exhaustion and apoptosis of T cells [8,9]. PD-1 is also expressed on a subset of thymic T cells, NK cells, B cells, monocytes and dendritic cells [8,10,11,12]. The main ligand of PD-1 is PD-L1, which is an important member of the B7/CD28 costimulatory factor superfamily and is expressed on T cells, dendritic cells and macrophages in order to regulate an adequate immune response [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 is expressed on activated T cells and interacts with its ligands PD-L1 (B7-H1) and PD-L2 (B7-DC), leading to the reduced proliferation, exhaustion and apoptosis of T cells [8,9]. PD-1 is also expressed on a subset of thymic T cells, NK cells, B cells, monocytes and dendritic cells [8,10,11,12]. The main ligand of PD-1 is PD-L1, which is an important member of the B7/CD28 costimulatory factor superfamily and is expressed on T cells, dendritic cells and macrophages in order to regulate an adequate immune response [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…12 So far, only limited clinical data are available on the pattern of PD-L1 or PD-1 expression on T cells in patients with myeloid disease. 13 We found that PD-L1 and PD-1 expression also increased on PB-and BM-derived T cells during PEM therapy (Figure 2C-F; supplemental Figure 1). The direct relationship of these findings to PEM therapy is supported by the observation that T cells also showed a marked reduction of PD-L1 and PD-1 expression in PB during treatment interruption.…”
Section: Resultsmentioning
confidence: 75%
“…Previous studies have shown that TCR repertoire deficiency is a common characteristic of patients with leukemia, including those with T-ALL (12,46). Potential reasons for deficiencies in the TCR repertoire include: i) The prior proliferation of a malignant T-cell clones suppressed the proliferation of normal T-cell clones, and ii) the tumor microenvironment or other unknown factors affect the competency of the immune system (47,48). However, the T-cell repertoire deficiency was not significantly reconstituted even when the patient achieved CR, as the reconstitution of the TCR repertoire is slow due to the cytotoxicity of chemotherapy (49).…”
Section: Discussionmentioning
confidence: 99%